Literature on Wearable Technology for Connected Health: Scoping Review of Research Trends, Advances, and Barriers - Loncar-Turukalo, Tatjana; Zdravevski, Eftim; Machado da Silva, José; Chouvarda, Ioanna; Trajkovikj, Vladimir (JMIR Publications Inc., 2019)
Wearable sensing and information and communication technologies are key enablers driving the transformation of health care delivery toward a new model of connected health (CH) care. The advances in wearable technologies in the last decade are evidenced in a plethora of original articles, patent documentation, and focused systematic reviews. Although technological innovations continuously respond to emerging challenges and technology availability further supports the evolution of CH solutions, the widespread adoption of wearables remains hindered.